Design of a 2 HP Power Waste Shutter Machine Using on-Grid PLTS With 6 x 290 WP - Pangalitan, Agung; Samosir, Rahmad; Pane, Medyawati (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
In the campus environment, the management of organic waste such as leaves is of particular concern, so a 2 HP organic waste shredder was designed with a rotation speed of 1450 rpm, a 150 mm diameter pulley, and a 6200 mm long shaft with 21 blades 15 mm thick, 25 mm wide, 100 mm long, and 24 mm diameter motor shaft made of S45C steel, supported by a 1.47 kW motor; Testing of this machine at various waste loads shows optimal results with different electrical power and engine rotation, such as at loads of 0.2 kg (237.8 V, 6.27 A, 1.49 kW), 3.5 kg (184 .1 V, 5.97 A, 1.15 kW , 1493 rpm), 5 kg (221.2 V, 6.37 A, 1,409 kW, 1990 rpm), and 8 kg (234.6 V, 6.38 A, 1,496 kW), so that this machine is supported by an on-grid PLTS with a power of 1740 WP which is able to increase the efficiency of electricity costs for the needs of operating the chopping machine. Keywords: 2HP AC motor; organic chopping machine